Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1034/j.1600-0579.2003.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to promote continuing professional development for dentists

Abstract: An effective method of facilitating change in quality dental practice was identified. Assessment of strategies and techniques for professional development of dentists should include observation of patterns of participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Research strategies such as clinical audits and interviews may be more appropriate tools for such evaluations and provides scope for future research strategies. [25][26][27][28] The design of the delayed questionnaire was based initially on a survey instrument used in a previous study, 19 with generic questions used for both disciplines to assess if the programmes impacted on clinical practice. The use of more detailed discipline-specific questions similar to what was used in the pre-CPD questionnaires may have facilitated the identification of more specific changes to clinical practice (e.g., rubber dam usage, types of irrigant used, implant treatment planning philosophies).…”
Section: Discussionmentioning
confidence: 99%
“…Research strategies such as clinical audits and interviews may be more appropriate tools for such evaluations and provides scope for future research strategies. [25][26][27][28] The design of the delayed questionnaire was based initially on a survey instrument used in a previous study, 19 with generic questions used for both disciplines to assess if the programmes impacted on clinical practice. The use of more detailed discipline-specific questions similar to what was used in the pre-CPD questionnaires may have facilitated the identification of more specific changes to clinical practice (e.g., rubber dam usage, types of irrigant used, implant treatment planning philosophies).…”
Section: Discussionmentioning
confidence: 99%
“…In general, physicians are closer to QA/I systems than dentists possibly because most dental services are provided by the private sector 11,49 . Formal mechanisms for assessing the continued competency and performance of dentists and for distinguishing the quality of services tend not to exist outside hospitals 1 .…”
Section: Qa/i and Dentistrymentioning
confidence: 99%
“…It is as yet unclear how quality of oral care in dental practice can be improved. Research data on effectiveness of interventions to promote continuing professional development for dentists are rare [17]. A previous study showed that small group education sessions did not change dentists' clinical behaviour [20].…”
Section: Introductionmentioning
confidence: 99%